2022
DOI: 10.1007/s12031-021-01962-z
|View full text |Cite
|
Sign up to set email alerts
|

6-Hydroxydopamine Induces Neurodegeneration in Terminally Differentiated SH-SY5Y Neuroblastoma Cells via Enrichment of the Nucleosomal Degradation Pathway: a Global Proteomics Approach

Abstract: The SH-SY5Y human neuroblastoma cells have been used for decades as a cell-based model of dopaminergic neurons to explore the underlying science of cellular and molecular mechanisms of neurodegeneration in Parkinson’s disease (PD). However, data revealing the protein expression changes in 6-OHDA induced cytotoxicity in differentiated SH-SY5Y cells remain void. Therefore, we investigated the differentially regulated proteins expressed in terminally differentiated SH-SY5Y cells (differ-SH-SY5Y neural cells) expo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…It can be suggested that activation of autophagy contributes to the alleviation of PD by regulating VDAC1; however, there is no VDAC1-specific autophagy activator. Studies on PD patients, research by Chu et al, and our current study have shown that VDAC1 expression is downregulated during PD [60], but VDAC1 expression is not downregulated in vivo and in vitro models of PD [41,42,59,[78][79][80][81]. We speculate that VDAC1 may be a double-edged sword playing different roles in PD.…”
Section: Limitationssupporting
confidence: 49%
See 1 more Smart Citation
“…It can be suggested that activation of autophagy contributes to the alleviation of PD by regulating VDAC1; however, there is no VDAC1-specific autophagy activator. Studies on PD patients, research by Chu et al, and our current study have shown that VDAC1 expression is downregulated during PD [60], but VDAC1 expression is not downregulated in vivo and in vitro models of PD [41,42,59,[78][79][80][81]. We speculate that VDAC1 may be a double-edged sword playing different roles in PD.…”
Section: Limitationssupporting
confidence: 49%
“…However, the details of this protective mechanism remain unmapped. In addition, there is an increase in the expression of VDAC1 in the PD cell model induced by rotenone [ 78 ], 1-methyl-4-phenylpyridinium (MPP + ) [ 79 ], and 6-hydroxydopamine (6-OHDA) [ 80 ]. A recent study has revealed that vitamin D has neuroprotective effect on PD model of rats induced by 6-OHDA by decreasing the upregulation of VDAC1 [ 81 ].…”
Section: Vdac1 and Pdmentioning
confidence: 99%
“…These proteins were analyzed based on changes in the biological processes of the GO term classification cluster. According to GO biological process analysis, upregulated proteins in 6-OHDAtreated SH-SY5Y cells respond to external stress, and as previous studies have shown (Magalingam et al 2022), proteins that regulate ribosomal assembly were upregulated. These results were consistent with reactome gene set analysis (Fig.…”
Section: Bioinformatics Analysis Of Depsmentioning
confidence: 82%
“…However, the mechanism underlying 6-OHDA-and MPP+-induced injury remains unclear. Previous studies have only reported the effects of 6-OHDA and MPP+ on neuronal cells separately (Blum et al 2001;Perfeito et al 2013;Xie et al 2011;Komatsubara et al 2012;Choi et al 2014;Alberio et al 2014;Magalingam et al 2022), and none of them have directly compared the effects of 6-OHDA and MPP+ on neuronal cells. Thus, large-scale proteome investigation of the effects of 6-OHDA and MPP+ on neuronal cells will bring new insights into PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation